The Impact of Entrepreneurship Education on Unemployment Rate in the South East Nigeria - Ugobueze, Ann Ngozi; Okwunmuo, Victoria N (Lembaga Riset Mutiara Akbar (LARISMA), 2024)
The study investigated the impact of entrepreneurship education on unemployment rate in the South Eastern region of Nigeria. It unfolds the benefit of acquiring income through self-employment of any acquired entrepreneurship skills using the five states that made up the South Eastern region of Nigeria which are Anambra, Imo, Ebonyi, Enugu, and Abia State. The study adopts a survey research design in which a validated items questionnaire termed the Entrepreneurship Skills (ESE) education would be developed in line with the research questions and used to elicit information on the categories of the population of students in the selected schools. The SS3 students selected from the five states would be used for the study. The Cronbach alpha statistics, the simple regression and the t-test would be used to analyze generated data for the study. The results showed that entrepreneurship education has a significant impact on reducing unemployment in Southeast Nigeria. The highest mean score of 3.47 reflects the strong influence of skills in identifying market needs and developing solutions. Networking opportunities (M = 2.95) and practical skills training (M = 2.94) also contribute positively. However, equipping individuals to create businesses (M = 2.26) and empowering youth to create jobs (M = 2.33) show lower influence. The analysis reveals that while entrepreneurship education significantly supports youth employment readiness, gender plays a more substantial role than age in the perceived benefits and opportunities created through entrepreneurship education. Conclusively, the research underscores the critical role of entrepreneurship education in promoting economic empowerment and suggests policy recommendations to strengthen these educational initiatives in Southeast Nigeria.